IDENTIFIKASI DAN POPULASI LALAT BUAH Bactrocera spp. PADA AREAL TANAMAN CABE, TOMAT, DAN LABU SIAM - Kaurow, Hetsi A.; Tulung, Max; Pelealu, Jantje (Universitas Sam Ratulangi, 2015)
ABSTRACT Improvements to the identification techniques adapted to the latest determination key, requires socialization, so that the farmer can determine which plant pests have damaged many crops and causing losses. This study were conducted to determine species of fruit fly Bactrocera spp. and to determine the population of Bactrocera spp. attacking commodities chili, tomato and pumpkin siam. Research carried out by direct surveys on the area which is the center of the fruit and vegetable crops in Tomohon. Each stretch of the plants fruit vegetable crops of chili, tomato and pumpkin siam was laid trap.Â The number of traps on each observation plots of vegetables or fruit per plant commodities were 5 (five) traps. The bottle trap was placed in the middle of planting vegetables fruit by a diagonal way. Traps of steiner models made of plastic bottles of 1.5 liters of mineral water and a perforated plastic funnel fitted as entrance fruit flies was used in this experiment. The tool is also equipped with a wire as a binder between the traps and wood enforcement to be put in planting fruit vegetables. Cotton was rolled with a diameter of about 3 cm and then tied with thread and put Methyl Eugenol (ME) of 0.25 ml and Cue-Lure (CL) as much as 0.25 ml by using the syringe and then hung in the middle of the bottle trap. Keywords : identification, population, Methyl Eugenol, Cue-Lure